Rapid loss of firn pore space accelerates 21st century Greenland mass loss. Issue 10 (23rd May 2013) - van Angelen, J. H.; M. Lenaerts, J. T.; van den Broeke, M. R.; Fettweis, X.; van, E.
Abstract [1] Mass loss from the two major ice sheets and their contribution to global sea level rise is accelerating. In Antarctica, mass loss is dominated by increased flow velocities of outlet glaciers, following the thinning or disintegration of coastal ice shelves into which they flow. In contrast, 55% of post‐1992 Greenland ice sheet (GrIS) mass loss is accounted for by surface processes, notably increased meltwater runoff. A subtle process in the surface mass balance of the GrIS is the retention and refreezing of meltwater, currently preventing 40% of the meltwater to reach the ocean. Here we force a high‐resolution atmosphere/snow model with a mid‐range warming scenario (RCP4.5, 1970–2100), to show that rapid loss of firn pore space, by >50% at the end of the 21st century, quickly reduces this refreezing buffer. As a result, GrIS surface mass loss accelerates throughout the 21st century and its contribution to global sea level rise increases to 1.7 ±0.5 mm yr−1, more than four times the current value.